PP.10.19: AMBULATORY BLOOD PRESSURE PROFILES IN VERY ELDERLY SUBJECTS IN COMPARISON WITH YOUNG ONES. (June 2015) - Agrati, A.; Colombo, F.; Beltrami, L.; Palmieri, G.; Ferraro, G.
Abstract : Objective: Ambulatory blood pressure monitoring (ABPM) is being increasingly used in the assessment of hypertension in all age groups, confirming the continuous relationship between blood pressure (BP) and cardiovascular risk amongst older people. Moreover, ABPM seems to be is a more accurate predictor of cardiovascular morbidity and mortality than clinic measurements, providing a better estimate of BP load and identification of white-coat hypertension, a known common phenomenon in the elderly. The present analysis was undertaken to evaluate blood pressure profiles in subjects over 80 years old referred to our institution for ABPM in comparison with young subjects (18–30 years old). In view of the lack of data regarding ABPM in elderly people, we tried to better understand additional value of ABPM over office BP measuring and its reflections on patients' treatment and follow-up. Design and method: 429 ABPMs of subjects aged 80 and over compared with 210 ABPMs of subjects between 18 and 30 years, referred at our Institution in the period 2000- 2014 were analyzed; all the recordings were performed using the same oscillometric device (TM 2430), in order to avoid confounding factors; all ABPMs fulfilled both the following criteria: > 23 hours recording and at least 2 valid measurements/hour (>70 % of total measures). Results: We identified hypertensive and normotensive subjects; hypertensives were furtherly subdivided in white coat, masked, isolated systolic, systo-diastolic and diastolic isolated hypertensives. Dipper and non dipper status (difference day- night > 10%) and post prandial fall were also calculated. Morning surge phenomenon and hypotension were also considered. Conclusions: Twenty-four-hour ABPM provides many measurements for better analysis and is likely to eliminate the stress of office visits and observer bias and proves to be a more accurate predictor of target organ damage and cardiovascular risk than routine office BP measurements. This tool seems to be of a certain importance even in the better evaluation of elderly subjects and in their possible therapeutic approach. White coat phenomenon seems to be a crucial parameter to be taken into account not only in younger subjects but also in elderly.